A facile and general approach for production of nanoscrolls with high-yield from two-dimensional nanosheets. Issue 1 (December 2018) - Wang, Wucong; Gai, Yanzhe; Xiao, Ding; Zhao, Yaping
Abstract Nanoscrolls (NSs) assembled from two-dimensional nanosheets have emerged as a novel type of one-dimensional nanomaterials because of their unique topological features and properties. The scale-up preparation of the NSs is crucial for their foundational and applied research. Herein, we report a general and straightforward approach for efficiently converting two-dimensional nanosheets into the NSs with high yield. We demonstrated the converting process by illustrating the formation of the graphene nanoscrolls through characterizing their morphology and structure using a scanning electron microscope, transmission electron microscope, Raman spectra, and X-ray diffraction spectra. The graphene sheets with a few-lay number were converted immediately and entirely into the graphene nanoscrolls when they mixed with an ethanol solution of silver nitrate at room temperature. The as-prepared graphene nanoscrolls were confirmed to be formed via the layer-by-layer assembly of graphene triggered by silver cyanide formed in site. Also, we extended this approach to construct the nanoscrolls of the hexagonal boron nitride, molybdenum disulfide, and tungsten disulfide, respectively, from their corresponding two-dimensional nanomaterials. In a broader context, this approach paves a significant new way for the large production of the NSs with cost-efficiency.